TALEN-mediated targeted mutagenesis of more than 100 COMT copies/alleles in highly polyploid sugarcane improves saccharification efficiency without compromising biomass yield - Kannan, Baskaran; Jung, Je Hyeong; Moxley, Geoffrey W.; Lee, Sun-Mi; Altpeter, Fredy (Blackwell Publishing Inc., 2018)
Sugarcane is the world's most efficient feedstock for commercial production of bioethanol due to its superior biomass production and accumulation of sucrose in stems. Integrating first- and second-generation ethanol conversion processes will enhance the biofuel yield per unit area by utilizing both sucrose and cell wall-bound sugars for fermentation. RNAi suppression of the lignin biosynthetic gene caffeic acid O-methyltransferase (COMT) has been demonstrated to improve bioethanol production from lignocellulosic biomass. Genome editing has been used in a number of crops for creation of loss of function phenotypes but is very challenging in sugarcane due to its highly polyploid genome. In this study, a conserved region of COMT was targeted with a single-transcription activator-like effector nuclease (TALEN) pair for multi-allelic mutagenesis to modify lignin biosynthesis in sugarcane. Field-grown TALEN-mediated COMT mutants showed up to 19.7% lignin reduction and significantly decreased syringyl to guaiacyl (S/G) ratio resulting in an up to 43.8% improved saccharification efficiency. Biomass production of COMT mutant lines with superior saccharification efficiency did not differ significantly from the original cultivar under replicated field conditions. Sanger sequencing of cloned COMT amplicons (1351-1657 bp) revealed co-editing of 107 of the 109 unique COMT copies/alleles in vegetative progeny of line CB6 using a single TALEN pair. Line CB6 combined altered cell wall composition and drastically improved saccharification efficiency with good agronomic performance. These findings confirm the feasibility of co-mutagenesis of a very large number of targetalleles/copies for improvement in crops with complex genomes.